(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the epidemiological, clinical, and paraclinical characteristics of gastric cancer patients undergoing laparoscopic total gastrectomy at Cho Ray Hospital. Methods: A prospective descriptive study was conducted on 74 patients diagnosed with gastric cancer who underwent laparoscopic total gastrectomy at the Department of Gastrointestinal Surgery, Cho Ray Hospital from October 2023 to October 2025. Data on epidemiological, clinical, and paraclinical characteristics were collected and analyzed using SPSS 22.0. Results: The proportion of male patients was 55.4%, with a mean age of 59.03 ± 9.75 years; the 60-69 age group accounted for the highest proportion (44.6%). The primary occupation is farming (52.7%), and the majority of patients come from provinces and cities outside Ho Chi Minh city (85.1%). Tumors were most commonly located in the gastric body (63.5%). Abdominal pain was the most frequent symptom (100%), followed by weight loss (24.3%) and anemia (17.6%). The mean duration of symptoms was 1.27 ± 0.68 months, with 75.7% presenting within 1 month. Most patients had relatively preserved hematological and nutritional status before surgery. On endoscopy, ulcerative-proliferative lesions were predominant (48.6%), and adenocarcinoma was the most common histological type (93.2%), with moderately differentiated tumors accounting for the highest proportion (64.9%). Conclusion: Patients undergoing laparoscopic total gastrectomy for gastric cancer were predominantly older males with tumors mainly located in the gastric body. Abdominal pain was the most common presenting symptom. Most patients had relatively stable preoperative conditions. Endoscopic and histopathological findings were consistent with advanced gastric cancer, with adenocarcinoma being the predominant type.